Teaching pronunciation in the Indonesian context: A native speaker or ELF model? - Risa Fitria (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2020)
Today, the numbers of English speakers are geographically and culturally diverse. The discussion on which pronunciation model of English should be introduced to learners of English has become under discussion among English language practitioners. Should English teachers teach pronunciation aiming at near native accents or at intelligibility in which learners can understand different models of English? As a country where English is a foreign language and Non Native-English-Speaking Teachers (NNESTs) are vastly available, Indonesia has posed its uniqueness due to its diverse learners’ and teachers’ backgrounds. Under this circumstance, then, there has been a frequent question to whether NNESTs can help learners to develop their English pronunciation. This paper discusses English as a Lingua Franca (ELF) model as suggested by Jenkins (2000) in teaching English pronunciation that can be implemented in the Indonesian context. It suggests that what matters more to learners is improving their intelligibility in English pronunciation rather than aiming for near native accents. English teachers are encouraged to develop a pronunciation instruction that suits the learners’ needs and interests without discriminating any model of English. Finally, a conclusion is provided with my argument that ELF model will be a better model to be implemented in the teaching of pronunciation in the English classroom in Indonesia.